Social Support and Postpartum Depression in Human Immuno Deficiency Virus (HIV) Patients: Hubungan Dukungan Sosial terhadap Depresi Pascapersalinan pada Pasien Human Immuno Deficiency Virus (HIV) - Wahyudi Wahyudi; Yudianto B Saroyo; Jose MS Adjie; Sylvia D Elvira (Indonesian Socety of Obstetrics and Gynecology, 2014)
Objective: To evaluate the relationship between social support given to HIV patients with the incidence of postpartum depression. Method: All HIV patients who had delivery in Dr. Cipto Mangunkusumo hospital and Prof. dr. Sulianti Saroso hospital during the period of October 2012 to March 2013 were enrolled as research subjects. We performed depression screening with the Edinburgh Postnatal Depression Scale (EPDS) and to measure the social support provided by Social Support Questionnaire/Kuesioner Dukungan Sosial (KDS). Statistical analysis was done using Fisher’s exact test, Chi-square and unpaired t-test. Result: We found a total of 34.1% of subjects who experienced postpartum depression, in which 40% did not received proper social support. Considering the demographic characteristics of the subjects who experienced depression, 70% was in age group 20-35 years, 56.7% of subjects had low education level and 70% was primiparous. Conclusion: Social support has a protective effect towards postpartum depression in HIV patients. Keywords: Edinburgh postnatal depression scale, HIV, (kuesioner dukungan sosial), postpartum depression, social support